Molecular insights and Therapeutic prospects for the targeted treatment of Rheumatoid arthritis through in silico investigation of bioactive substances from Eranda (Ricinus communis Linn). (International Journal of Environmental Sciences, 2025)
Numerous studies indicate that Eranda (Ricinus communis Linn) has anti-inflammatory, anti-diabetic, and anti-fertility properties in addition to its ability to scavenge free radicals. Eranda's favourable qualities make it an excellent choice to be used as a medication for rheumatoid arthritis. Molecular docking technology and network pharmacology were used, however, in order to have a thorough grasp of how the various active plant compounds present in Eranda combine to produce therapeutic effects on RA. Through data mining, 25 active Eranda phytoconstituents and 36 IHD-intersecting genes were identified, and they were then further investigated for network pharmacology study. Thus, we discovered three key chemicals (Quercetin, Ellagic acid, and Apigenin) and three key targets (EGFR, SRC, and PDGFRA). A common-target enrichment study was then performed. The Purine metabolism pathway, the VEGF Signalling pathway, and the EGFR tyrosine kinase inhibitor resistance system were the main pathways that were modified, according to the KEGG enrichment data. Three core chemicals from Eranda: Apigenin, Ellagic Acid, and Quercetin has demonstrated a strong affinity for core target active sites. EGFR, SRC, and PDGFRA, according to the molecular docking studies, which also exhibited good docking scores. This investigation revealed Eranda's pharmacological and molecular modes of action against rheumatoid arthritis. Additionally, the study provided a theoretical framework for further research on the pharmacological targets and processes of Eranda.